Environmental Conservation Education through Biopore Introduction for Elementary School Students at Sanggar Belajar Kuala Lumpur - Handajani, Mudjiastuti; Rohadi, Rohadi; Pramucitra, Sinta Pramucitra; Pinandita, Satria; Anwar, Nik Syahrim Nik (Journal of Community Empowerment, 2025)
As the capital of Malaysia, Kuala Lumpur has not escaped various environmental issues that have worsened due to rapid urbanization, ranging from air pollution to insufficient waste management. This condition requires a creative solution to foster awareness of sustainability from a young age. In response, a community service program titled "Education for Environmental Conservation through the Introduction of Biopori for Elementary School Students at the Kuala Lumpur Learning Studio" was present to introduce the concepts and benefits of biopori technology to children aged 6 to 12. Its main goal is to build early awareness of environmentally friendly practices, especially in flood prevention and organic waste management. Methods used in the program vary widely and interactively, including storytelling, exciting visual presentations, educational games, and video demonstrations. The implementation of this program also collaborates with the Kuala Lumpur Indonesian School (SIKL), which ensures the harmony of culture and education with the target students. The results of the program showed a significant improvement in students' understanding and interest in biopore technology. Many of them are enthusiastic about implementing biopore at home, reflecting expected positive behavioral changes. Post-activity feedback from students and facilitators indicated high levels of engagement and enthusiasm. This initiative demonstrates the effectiveness of early environmental education in building eco-conscious habits. It supports the advancement of community-based science education and contributes directly to the Sustainable Development Goals (SDGs), particularly in clean water and sanitation (Goal 6) and climate action (Goal 13). The program offers a scalable model for integrating environmental awareness into urban education systems.